Complexing hemp seed protein with pectin for improved emulsion stability. Issue 7 (22nd June 2021) - Feng, Yiming; Yu, Dajun; Lin, Tiantian; Jin, Qing; Wu, Jian; Chen, Chengci; Huang, Haibo
Abstract : Abstract: Hemp seed protein has the potential to be used in food systems as an emulsifying agent; however, there are still some shortcomings associated with hemp seed protein, such as poor solubility and tendency to aggregate. This study aims to improve the dispersibility of hemp seed protein as an emulsifier by complexing with pectin, driven by electrostatic force. Three protein to pectin ratios were used for complexation, from 1:1, 2:1 to 4:1. The complexation improved the polydispersity of hemp seed protein when dispersed in the aqueous phase. The hemp seed protein displayed multimodal size distribution in water at pH = 3.0 due to aggregation, while the incorporation of pectin helped to diminish those aggregated proteins. When the hemp seed protein was used to stabilize the oil‐in‐water emulsion, its stabilized emulsion showed promising homogenous droplet size distribution after emulsification. However, during the accelerated storage conditions (55°C), the emulsion stabilized solely by hemp seed protein was subjected to extensive coalescence. From day 0 to 9, the droplet size (d4, 3 ) increased by 50 folds from 3.215 to 161.6 µm. In contrast, the hemp seed protein–pectin complex exhibited extraordinary stability during the storage test, where size evolution in all three samples was negligible compared to the emulsion stabilized by hemp seed protein. Rheological characterization suggests that pectin provided physical strength, which may help the emulsion droplets to maintain structural integrity under environmental stress. The underlying mechanism could be associated with the formation of a three‐dimensional structure by pectin through bridging adjacent emulsion droplets. Practical Application: Hemp seed protein is gaining more and more attention as an emerging plant protein. Recently, hemp seed protein has been explored as an emulsifier, but its stabilized emulsion encounters instability issues during storage. Our study suggests pectin could be used as a co‐stabilizer for hemp seed protein emulsions.